PERAN PEMBIMBING KEMASYARAKATAN DALAM MENANGANI KASUS ANAK BERHADAPAN DENGAN HUKUM (Studi Kasus Balai Pemasyarakatan Kelas II Magelang) - Melati, Resta; Mey Lia Sari; Nadia Ardine; Arifa Kurnia Sari ISSP; Wahyu Prabowo (Cahaya Ilmu Bangsa, 2024)
Abstract During the 2023 period, the Class II Magelang correctional center received requests for 83 community research cases regarding children, the most cases of which occurred were cases of theft, brawls and sharp weapons. When dealing with children who are in conflict with the law, they need assistance from state officials such as community counselors. This research was conducted with the aim of finding out how important a role community counselors play in the juvenile justice process through the perspective of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. The method used is qualitative research, namely carrying out a case study approach. In this research, data collection used data collection techniques through documentation, interviews and observations carried out from January to February. The results of this research show that the role of community counselors in the juvenile justice process is very crucial, even though there are several obstacles in guiding child clients. The Magelang Correctional Center can prove that these obstacles are not a big problem, this is proven by the achievement of 1st place in the best UPT in terms of pursuing interests. best for children in 2023